Real-time detection of aortic valve in echocardiography using convolutional neural networks - Nizar M.H.A.; Chan C.K.; Khalil A.; Yusof A.K.M.; Lai K.W. (Bentham Science Publishers, 2024)
Indexed by WOS/ Scopus